Maintaining Faithfulness Amidst the Temptations of the World - Siburian, Faramita (Hikmat : Jurnal Agama Kristen, 2024)
Human life in this world is always filled with various forms of temptation that can shake faith and loyalty to God. In the era of globalization and rapid social development, Christians face a major challenge to remain steadfast in their faith amidst worldly values ​​that often contradict the truth of God's word. This study aims to explore the meaning of faithfulness in the Christian faith and how believers can maintain their spiritual commitment amid various worldly temptations such as hedonism, materialism, and moral compromise. Using a theological and reflective approach, this study highlights the role of prayer, God's word, church community, and the example of Jesus Christ as sources of strength to maintain faithfulness in the faith. The results of the study show that true faith is not merely belief, but concrete actions manifested through obedience and loyalty to God in all life situations.